THE EFFECT OF USING E-COMMERCE, DIGITAL PAYMENT AND THE QUALITY OF ACCOUNTING INFORMATION SYSTEMS ON ENTREPRENEURIAL INTEREST: (Study on Students of Accounting Department, Faculty of Economics and Business, Jambi University) - Yulia Sapitri; Ilham Wahyudi; Yudi Yudi (Transpublika Publisher, 2024)
The integration of e-commerce, digital payments, and Accounting Information Systems significantly enhances entrepreneurial interest among students. These technologies provide accessible and efficient tools for starting and managing businesses, fostering a greater inclination towards entrepreneurship. This study aims to analyze the influence of e-commerce, digital payment, and the quality of Accounting Information Systems (AIS) on the entrepreneurial interest of accounting students from the 2020 cohort at the University of Jambi. A saturated sampling technique was employed, resulting in a sample size of 171 active accounting students. Data collection was conducted through an online questionnaire consisting of several relevant questions. The results of the study indicate that e-commerce, digital payment, and the quality of AIS significantly affect students' entrepreneurial interest. These findings suggest that a good understanding and skills in using digital technology and information systems can encourage students' interest in entrepreneurship. Likewise, improving students' proficiency in online business, digital transactions, and computerized accounting can substantially boost their enthusiasm for entrepreneurship. Such skill development may result in more students starting their own businesses, potentially stimulating economic expansion and helping to lower joblessness among recent graduates.